A NEW SPECIES OF HYLODES FROM SOUTHEASTERN BRAZIL (AMPHIBIA, LEPTODACTYLIDAE) - Haddad, CFB; Pombal, J. P. (Herpetologists League, 1995)
A new species of leptodactylid frog is described from the Serra das Cabras in São Paulo, southeastern Brazil. The new species is a member of the Hylodes lateristrigatus group and is characterized by its small size and high number of notes per call. Descriptions of the tadpole and advertisement call and information on natural history are provided.
Keywords: ANURA; LEPTODACTYLIDAE; HYLODINAE; ADVERTISEMENT CALL; NEW SPECIES; SOUTHEASTERN BRAZIL; TADPOLE